Analisis Nilai Moral dan Nilai Sosial pada Kumpulan Cerpen Karya Ahmad Tohari sebagai Upaya Pemilihan Bahan Pembelajaran pada Siswa Kelas X SMAN 5 Pandeglang - Trisnawati, Trisnawati (Universitas Mathla'ul Anwar Banten, 2018)
The study aims to determine the moral values and social values in a collection of short stories by Ahmad Tohari as learning material in class X SMAN 5 Pandeglang. The aim of this study to 1) Provide knowledge about the values contained in short story, 2) Growing motivation in reading short story literature, 3) Increasing interest in appreciating short stories, 4) Able to analyze the values contained in short story literature, 5) Instill the positive values of short stories in everyday life. The method used in this research is descriptive analysis method. Descriptive method is the method used to make broader conclusions. Research data collection techniques were carried out using literature studies or documentation studies on Ahmad Tohari’s short stories. The steps in this descriptive study are, 1) Identify significant problems that can be solved through the descriptive method, 2) Formulate the problem clearly, 3) Determine the purpose and benefits of research, 4) Conduct literature studies related to problems, and 5) Collect and analyze data qualitatively. The steps of data collection are reading Ahmad Tohari’s short stories carefully, recording the appropriate data, identifying and classifying data and making data education. The results of the study indicate that the collection of short stories by Ahmad Tohari contains many values, especially moral values and social values.